Sensitivitas Barorefleks pada Penderita Penyakit Jantung Koroner yang Menjalani Intervensi Koroner Perkutan - Cholid Tri Tjahjono; Muhammad Munawar; RWM Kaligis; Idris Idham (Jurnal Kardiologi Indonesia, 2007)
Background.Autonomic dysfunction contributes to incidence of ventricular arrhythmias and sudden cardiac death in patients with coronary artery disease (CAD). Revascularization, for example percutaneous coronary intervention (PCI), is intended to improve myocardial perfusion. Besides that, PCI is considered to improve autonomic dysfunction. This study is aimed at assessing baroreflex sensitivity (BRS) in patients with CAD before and after PCI.Methods. Patients with angiographically having coronary stenoses = 50% who underwent coronary angioplasty at the catheterization laboratorium of National Cardiovascular Center Harapan Kita, Jakarta, were included in this study. Baroreflex sensitivity was calculated by administering nitroglycerin 300 µg intra aortic before and after PCI.Results.Subjects comprise of 8 (42%) male and 11 (58%) female, aged 57.5 ± 9.3 year old. Most of subjects had dyslipidemia (57%), were smoker (42%), had hypertension (42%) and only 3 (16%) had diabetes mellitus. Nine (47%) of subjects had previous history of myocardial infarction. Medications suspected affecting baroreflex sensitivity, which were used by the time of study included nitrate (63%), beta-blockade (58%), and calcium antagonist (32%). Mean value of baroreflex sensitivity pre-PCI and post-PCI were 2,51+3,23 ms/mmHg and 1,96+1,61 ms/mmHg (p=0,412), subsequently. Multivariate analysis with logistic regression showed that nitrate has significant effect on decreased BRS soon after PCI (p=0,023; CI 95% 1,496-216,62;OR 18,00).Conclusion. In patients with Coronary Artery Disease, immediately after percutaneous coronary intervention, barorefelex sensitivity was decreased. Nitrate has significant effect on alteration of barorefelex sensitivity.